Informal Sector and Tax Compliance in Nigeria- Challenges and Opportunities - Augustine, Adekoya, A.; Samuel, Olaoye, A.; Babatunde, Lawal, A. (International Journal of Emerging Trends in Social Sciences, 2020)
Taxing the Informal Sector (IS) and its taxpayers’ compliance level has become a focus of attention in recent times by scholars and policy makers because of IS contribution to the country. IS seems difficult to tax because of administrative problems, human capital and personnel shortage, lack of record keeping, nature of its economic activities and cost implications. Therefore, there is need for better understanding of the concept, challenges, and methods of taxing, and of promoting tax compliance (TC) in the IS. It is against this background that the study examined IS and TC in Nigeria with its challenges and opportunities. Exploratory research design was adopted for the study with focus on literatures in the area of taxation, accounting and finance. The study concluded that taxing the IS is very important to any developing country as this achieved three things: revenue, growth and governance. Government needs to expand its tax net with much focus on the IS as any further neglect of this sector might dampen the moral of some individual taxpayers especially those in the formal sector who had been voluntarily paying tax. However, there is need for simplification of tax laws and establishment of tax courts, tax education and enlightenment, inter-agency collaboration and provision of Tax Identification Number (TIN), government should also exhibit accountability and transparency in order to build trust in the informal sector operators for tax compliance.